Advances in Wireless, Mobile Networks and Applications International Conferences, WiMoA 2011 and ICCSEA 2011, Dubai, United Arab Emirates, May 25-27, 2011. Proceedings - Al-Majeed, Salah S.; Hu, Chih-Lin; Nagamalai, Dhinaharan (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the Third International Conference on Wireless, Mobile Networks and Applications, WiMoA 2011, and the First International Conference on Computer Science, Engineering and Applications, ICCSEA 2011, held in Dubai, United Arab Emirates, in May 2011. The book is organized as a collection of papers from WiMoA 2011 and ICCSEA 2011. The 8 revised full papers presented in the WiMoA 2011 part were carefully reviewed and selected from 63 submissions. The 20 revised full papers presented in the ICCSEA 2011 part were carefully reviewed and selected from 110 submissions.